The Design of Buck-Boost Converter With Arduino Based on 8x10 Wp Photovoltaic Power Plant - Rajagukguk, Antonius; Fadil, Jazuli; Julianto, Jeffry (Electrical Engineering Department, Faculty of Engineering, Universitas Riau, 2021)
The use of solar panels through the Photovoltaic (PV) process is an efficient way to produce electrical energy. The main barriers to the use of solar panels are their low energy conversion efficiency and high initial costs. Solar panels are unregulated DC power sources that produce fluctuating voltages and currents, so they must be controlled properly in order to work as expected. Usually when solar panels are directly connected to a load, the operating point is rarely at its Maximum Power Point (MPP). Maximum Power Point Tracking (MPPT) is used to generate maximum power from solar panels. The DC to DC conversion functions as an intermediary for the solar panels and the load to deliver the maximum power to the load. In this study, MPPT was used with the Perturb & Observe (P&O) algorithm and DC to DC converter with a buck-boost converter type. Based on the test results between simulation and tool implementation, the input voltage of 17.6 V produces an output voltage of approximately 14.4 V for charging a 12 V battery with the maximum power produced by the PV generator. Based on these tests, it can be concluded that the buck-boost converter design based on the Arduino Uno in the 8x10 Wp photovoltaic power plant can work well.